(untitled) (Journal of Medicine, 2011)
A 40 yrs female muslim housewife attended Endocrinology department of Dhaka Medical College Hospital with the complaints of swelling in front of neck, alone with dryness of the skin, cold intolerance, constipation and menorrhagia. Physical examination and laboratory investigations substantiated the diagnosis of accessory thyroid gland in front of neck above the isthmus of the thyroid gland. RAIU and scanning showed normally present thyroid gland with accessory thyroidal nodular swelling in the midline in the upper part of front of neck .USG of the thyroid gland showed normal size of thyroid gland with coarse echo texture. A hypo echoic solid thyroid nodule was also seen above the isthmus of the thyroid gland, measuring about 2.4 cm×2.2cm. Thyroid function tests revealed hypothyroidism. She is on thyroid hormone replacement therapy. This rare presentation of accessory thyroid gland with hypothyroid state led us to report the case. Keywords: Accessory thyroid gland, Hypothyroidsm, Ectopic, Bangladesh DOI: http://dx.doi.org/10.3329/jom.v12i2.8426 JOM 2011; 12(2): 180-182